Decomposing the riskiness of corporate foreign currency lending: The case of Hungary - Dzsamila Vonnák (Hungarian Academy of Sciences, Institute of Economics, 2015)
I decompose the factors contributing to the riskiness of foreign currency borrowers. I compare counterfactual default probabilities of local and foreign currency borrowers estimated on disaggregated data. My results suggest that the currency mismatch with the depreciation of the local currency is the most important factor contributing to the riskiness of foreign currency borrowers, though boom-period excessive risk taking of banks is also concentrated in foreign currency lending.
Keywords: G21; F31; F34; 330; foreign currency debt; banking